Pulmonary cryptococcosis: An unusual presentation - Anand K Babu; Ram Gopalakrishnan; L Sundararajan (Lung India, 2013)
Cryptococcal infection of the lung is usually asymptomatic in immunocompetent hosts. Symptomatic cryptococcal lung infection presenting as an endobronchial mass lesion in an immunocompetent host is rare. We report our experience with an immunocompetent young patient presenting with an endobronchial mass lesion caused by cryptococcal infection. This male patient presented with left sided collapse, consolidation on computed tomography scanning, and was found to have a polypoid lesion in the left main bronchus. The diagnosis was confirmed by bronchial biopsy and the patient responded well to parenteral antifungal therapy. The case report is followed by a review of pulmonary cryptococcosis including clinical features, diagnosis, and treatment.